2021
DOI: 10.18632/aging.203538
|View full text |Cite
|
Sign up to set email alerts
|

AKR1B10 inhibits the proliferation and migration of gastric cancer via regulating epithelial-mesenchymal transition

Abstract: Gastric cancer (GC) is a common malignancy around the world with a poor prognosis. Aldo-keto reductase family 1 member B10 (AKR1B10) is indispensable to cancer development and progression, which has served as a diagnostic biomarker for tumors. In our study, we demonstrated that the expression of AKR1B10 in GC tissues was significantly lower compared with normal gastric tissues. Subgroup analysis showed that, according to the clinic-pathological factors, the effect of the AKR1B10 expression level on the prognos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 33 publications
(41 reference statements)
0
14
0
Order By: Relevance
“…To further verify the sequencing results, we performed a PCR array on MSCs and MSC SPIO to analyze the gene expression pattern in the ferroptosis-related signaling pathway. Among genes with significant fold-change, ferroptosis suppresser TF [ 24 , 25 ], and CA9 [ 26 , 27 ], were the most downregulated, and ferroptosis promoter AKR1B10 [ 28 ] was the most upregulated gene (Fig. 3C, D ).…”
Section: Resultsmentioning
confidence: 99%
“…To further verify the sequencing results, we performed a PCR array on MSCs and MSC SPIO to analyze the gene expression pattern in the ferroptosis-related signaling pathway. Among genes with significant fold-change, ferroptosis suppresser TF [ 24 , 25 ], and CA9 [ 26 , 27 ], were the most downregulated, and ferroptosis promoter AKR1B10 [ 28 ] was the most upregulated gene (Fig. 3C, D ).…”
Section: Resultsmentioning
confidence: 99%
“…However, the role of AKR1B10 remains unclear. Growing evidence has shown that AKR1B10 is a tumor suppressor [23,24]. Shao et al reported that AKR1B10 expression was significantly related to smaller tumor size, lower depth of invasion, negative lymph node metastasis, negative venous invasion, and advanced tumor stage [23].…”
Section: Discussionmentioning
confidence: 99%
“…Its knockdown could inhibit tumor proliferation and migration by enhancing epithelial-mesenchymal transition (EMT) in vivo. Furthermore, a high expression of AKR1B10 was significantly associated with a better 5-year survival rate [23,24]. In contrast, GC patients with overexpression of AKR1B10 were found to have advanced lymph node metastasis, fewer tumor regression, and worse overall survival (OS) than those without AKR1B10 expression [25].…”
Section: Introductionmentioning
confidence: 99%
“…We further predicted that miR-137 was correlated with the expression of Aldo-keto reductase family 1 member B10 (AKR1B10). AKR1B10 possesses potentials in cancer development and progression, which has emerged as a diagnostic target for tumors [ 12 ]. Furthermore, elevated AKR1B10 is detected in steatohepatitis [ 13 ], yet the effect of AKR1B10 on AH deserved explored in-depth.…”
Section: Introductionmentioning
confidence: 99%